Probing the SERS brightness of individual Au nanoparticles, hollow Au/Ag nanoshells, Au nanostars and Au core/Au satellite particles: single-particle experiments and computer simulations. Issue 46 (15th November 2018) - Tran, Vi; Thiel, Christian; Svejda, Jan Taro; Jalali, Mandana; Walkenfort, Bernd; Erni, Daniel; Schlücker, Sebastian
Abstract : Different classes of plasmonic nanoparticles are tested for their SERS signal brightness at the single-particle level. Abstract : Different classes of plasmonic nanoparticles functionalized with the non-resonant Raman reporter molecule 4-MBA are tested for their SERS signal brightness at the single-particle level: gold nanoparticles, hollow gold/silver nanoshells, gold nanostars, and gold core/gold satellite particles. Correlative SERS/SEM experiments on a set of particles from each class enable the unambiguous identification of single particles by electron microscopy as well as the characterization of both their elastic (LSPR) and inelastic (SERS) scattering spectra. Experimental observations are compared with predictions from FEM computer simulations based on 3D models derived from representative TEM/SEM images. Single gold nanostars and single gold core/gold satellite particles exhibit a detectable SERS signal under the given experimental conditions, while single gold nanoparticles and single hollow gold/silver nanoshells are not detectable.